The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s12866-016-0819-z
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of the carA gene in Pseudomonas syringae results in reduced fitness and alters motility

Abstract: BackgroundPseudomonas syringae infects diverse plant species and is widely used in the study of effector function and the molecular basis of disease. Although the relationship between bacterial metabolism, nutrient acquisition and virulence has attracted increasing attention in bacterial pathology, there is limited knowledge regarding these studies in Pseudomonas syringae. The aim of this study was to investigate the function of the carA gene and the small RNA P32, and characterize the regulation of these tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 75 publications
(78 reference statements)
0
9
0
Order By: Relevance
“…It has been observed that carA plays an important role in virulence in other bacterial species, such as Pseudomonas syringae ( 46 ), Escherichia coli ( 47 ), Xanthomonas citri ( 48 ) and Francisella tularensis ( 49 ). Similar to the genomic organization characterized in B. subtilis , several pyr genes ( pyR , pyrP , pyrB , pyrC , carA , carB , pyrF and pyrE ) of S. aureus are located on an operon and transcribed from a single promoter ( Figure 3B ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that carA plays an important role in virulence in other bacterial species, such as Pseudomonas syringae ( 46 ), Escherichia coli ( 47 ), Xanthomonas citri ( 48 ) and Francisella tularensis ( 49 ). Similar to the genomic organization characterized in B. subtilis , several pyr genes ( pyR , pyrP , pyrB , pyrC , carA , carB , pyrF and pyrE ) of S. aureus are located on an operon and transcribed from a single promoter ( Figure 3B ).…”
Section: Discussionmentioning
confidence: 99%
“…Genes adjacent (3′ end) to the short 5′UTRs identified in B. cenocepacia include homologues of genes known to harbour cis-regulatory structures in other bacterial species, e.g. ribonuclease E 34 (BCAL2888), a proline-betaine transporter 35 (BCAL1252), ribosomal proteins 36 (BCAL0115, BCAL2091, BCAL2765, BCAL2714, BCAL3348), carA 37 (BCAL1260) and tRNA-synthetases 36 (BCAL3373, BCAL3436). Attenuation, observed for many short 5′UTRs, is indicative of a cis-regulatory function.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, carAB , a component of the pyrimidine pathway, was downregulated by 17- and 10-fold relative to the control. As a part of the arginine and pyrimidine pathways, the carAB gene encodes the enzyme carbamoylphosphate synthetase (CPS), which catalyzes the synthesis of carbamoylphosphate (Piette et al, 1984; Martinussen and Hammer, 1998; Nicoloff et al, 2001; Butcher et al, 2016). Carbamoylphosphate is a common intermediate in arginine and pyrimidine biosynthesis (Werner et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact regulated mode of carAB in S. aureus is still unclear, similar studies performed on other gram-negative microbes suggest that arginine is likely involved in the regulation (Sekowska et al, 2001). Regulation of the carAB operon in P. aeruginosa is controlled by arginine and pyrimidines at the transcriptional level, possibly through an attenuation mechanism (Lu et al, 1997; Butcher et al, 2016). Further studies on E. coli identified an arginine box located upstream of the control region of carAB that served as the initiation site, but which was blocked upon arginine recognition (Piette et al, 1984; Crowell et al, 1987; Alwan et al, 2017).…”
Section: Discussionmentioning
confidence: 99%